Menghadapi Tantangan Global Berbasis Teknologi Melalui Modernisasi Pendidikan - F, Firman; Firmansyah, Rahmad; Sukma, Dina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The modernization of the education system in the digital era is a strategic necessity to address global challenges. This article examines technology-based educational transformation through a qualitative approach and literature review. The primary focus includes technology implementation Technology digital skill-based curricula, digital literacy, and the role of institutions such as Universitas Negeri Padang (UNP) in supporting this transformation. Despite challenges like technological access disparities, teacher readiness, and digital security, education modernization offers innovation opportunities through blended learning and data-driven education. This study emphasizes the importance of relevant scientific foundations, adaptive curriculum development, and progressive education policies. With a holistic approach, education modernization is expected to create a more inclusive, adaptive, and responsive system to global changes. Strategic recommendations are provided to support effective and sustainable implementation.